Energy dissipation in the magnetic fluid under the action of the field of acoustic frequency - Koskov, M.A.; Pshenichnikov, A.F. (Perm Federal Research Centre Journal, 2019)
The article presents the results of experimental studies of energy dissipation in a magnetic fluid in an alternating magnetic field of the acoustic frequency. The study aims at obtaining the information on the amplitude dependence of the dynamic susceptibility and the limits of applicability of the linear relaxation equation to magnetization. During the experiment a magnetic fluid purified from a coarse fraction by centrifugation was used. The measurements of heat release in a magnetic fluid with increased amplitudes of a magnetic field were carried out. A well-known formula relating the heat release power to an imaginary part of the susceptibility and which directly follows from the linear relaxation equation was used. The control direct measurements of the dynamic susceptibility were carried out with the use of the method of mutual inductance in a weak probing field with different values of the temperature of the magnetic fluid. The comparison of the results obtained by different methods did not reveal a significant discrepancy between the two series of experiments, which is explained by the substantial predominance in the solution of particles for which the Langevin parameter remains small with increased amplitudes of the probe field. As a result, the dynamic susceptibility remains quasi-independent of the field intensity up to at least 1,3 kA/m.